Increasing Public Access to University Qualifications: Evolution of The University of the West Indies Open Campus - Michael L. Thomas (Athabasca University Press, 2009)
This paper traces the evolution of The University of the West Indies’ Open Campus (UWIOC), which is expected to expand service and increase access to the underserved communities of the Eastern Caribbean. At present, UWI, which caters to the needs of the 16 far flung countries of the Commonwealth Caribbean, has not been able to fully serve these countries, the UWI-12, in a way that is commensurate with their developmental needs. Historically, the institution has been dominated by campus-based education, and its three campuses have been poles of attraction for scholars and scholarship to the significant advantage of the countries in which they are located: Jamaica, Trinidad and Tobago, and Barbados.